IN VITRO NEUTRALIZATION OF VIRULENCE PROPERTIES OF STREPTOCOCCUS MUTANS USING CHICKEN EGGYOLK ANTIBODIES (IGY) - GANDHIMATHI C; MICHAEL A (International Journal of Pharma and Bio Sciences, 2014)
Dental Caries is a cause global concern and India is no exception to this condition. The eruption of the teeth during the first few years leads to colonization by Streptococcus mutans. The present investigation was aimed to generate chicken eggyolk antibodies against antigens of S.mutans and to test their potential both in vitro to control the virulence of the cariogenic bacteria. The white leghorn chicken was immunized with each antigen, their eggs collected and the antibodies were purified. The titre of specific antibody was found to be 1:50000 on 56th Day. The protein concentration of the eggyolk was 40.20±0.70 mg/ml and the total IgY concentration of eggyolk was 20.74±0.38 mg/ml. Both anti-S.mutans IgY and anti-CA-GTF S.mutans IgY were able to prevent biofilm formation by Streptococcus mutans and to inhibit the sucrose dependant adherence of the bacteria to glass surfaces. Anti-CA-GTF S.mutans IgY was able to inhibit GTF activity of S.mutans higher than the control. The anti-CA-GTF and WC S.mutans IgY was able to neutralize in vitro the virulence properties of S.mutans.